The Influence of Perceived Integrity, Perceived Competence and Experience on Consumer’s Trust in Online Shopping in the Tulusrejo District of Malang City - Radyta Zahara; Lutfi Harris (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study examines the influence of perceived integrity, perceived competence and experience on consumer’s trust in online shopping in the Tulusrejo district of Malang city. The independent variables in this study are perceived integrity, perceived competence and experience. Consumer’s trust in online shopping is a dependent variable. The study to test the hypotheses on First Order Construct (FOC) used Partial Least Square (PLS) with sample are 295 peoples. Finally, the results found that perceived integrity, perceived competence and experience has a positive effect towards consumer’s trust in online shopping. Therefore, confidence (trust) of consumers to shop online will determine the consumer's decision to engage transaction or not. Lack of trust to shop online will reduce the willingness of consumers to do online transaction. Keywords: Perceived Integrity, Perceived Competence, Experience, Consumer’s Trust in Online Shopping